Evaluating key factors for the Private Vehicle Inspection (PVI) framework development in Malaysia - Abdul Jalil, Nawal Aswan; Abdul Aziz, Azizul; Md Rezali, Khairil Anas (Penerbit UTM Press, 2025)
Vehicles are one of the contributing factors to road crashes. Over the previous few decades, road crashes have claimed the lives of 6,540 people annually on average, and the government lost at least RM3.12 million for each life. To reduce the number of road fatalities, Private Vehicle Inspection (PVI) has been implemented voluntarily since 2013. PVI is an inspection carried out on private vehicles periodically to examine the vehicle condition and roadworthiness level. Although voluntary PVI has already been carried out, there is no appropriate framework for mandatory PVI implementation in the future as indicated in the National Automotive Policy (NAP), National Transport Policy (NTP) and Malaysia Road Safety Plan (MRSP). This study aimed to identify and analyse the key factors that influence the development of the PVI framework in Malaysia, to evaluate the importance level of each identified key factor and to identify the priority key factor. The key factors identified in this study were government readiness, PVI requirements, inspection centres, End-of-Life Vehicles (ELV), vehicle deregistration and vehicle disposal. The instrument used in this study consisted of a set of questionnaires containing 59 question items and using five-point Likert scales. Data were collected by distributing the questionnaires to six relevant ministries/agencies as the stakeholders. A total of 227 questionnaires out of 382 distributed were returned with a response rate of 59.4%. The results of the study were analysed using descriptive statistics and statistical tests. The study found that the important level of the key factors in influencing the PVI framework development was high. The study also revealed that the priority key factor identified was inspection centres. The results showed a moderate, positive correlation between inspection centres and PVI requirements, End-of-Life Vehicles (ELV), vehicle deregistration and vehicle disposal, which was statistically significant. The correlation between inspection centres and government readiness was weak, positive and statistically significant. The findings also showed a statistically significant difference in important levels depending on the combination of the priority key factor and other key factors. In conclusion, the most important key factor in developing the PVI framework in Malaysia was inspection centres. This study was limited to the responses from the perspective of the stakeholders, not including the public as a general respondent.